The Effect Of Compensation And Work Culture On Employee Performance Moderated By Work Motivation (Study On State Civil Apparatus Employees At The Cianjur Regency Regional Revenue Agency) - Ardian Athoillah; Maman Suratman (Jurnal Impresi Indonesia, 2025)
This research conducted to analyze the effect of Compensation and Work Culture on the Performance of State Civil Apparatus (ASN) employees, moderated by Work Motivation. The research was conducted on ASN employees at the Badan Pendapatan Daerah Kabupaten Cianjur. The research method used was descriptive verification. The sampling technique employed was saturated sampling, with a sample size of 42 respondents taken from the entire population. The data analysis technique used was multiple linear regression analysis using SPSS version 24 statistical software. This research was conducted through observation, interviews, and questionnaires, which served as guidelines for conducting interviews as a data collection technique. The results showed that Compensation and Work Culture have a positive and significant effect on the Performance of ASN employees, both partially and simultaneously. The analysis results indicate that Work Motivation strengthens the positive effect of Compensation on Employee Performance. However, Work Motivation, conversely, weakens the positive effect of Work Culture on Employee Performance. These findings suggest that fair and appropriate compensation, when combined with high Work Motivation, can improve Employee Performance. Nevertheless, high Work Motivation can reduce the effectiveness of implementing Work Culture in enhancing Employee Performance. This research provides practical implications for human resource management in the public sector, particularly in efforts to improve organizational performance quality through the provision of fair and appropriate compensation, the development of a positive work culture, and the enhancement of work motivation.